PENGARUH MODAL PSIKOLOGIS (PSYCAP) DAN BUDAYA ORGANISASI TERHADAP PERILAKU PRODUKTIF KEPALA SEKOLAH DASAR NEGERI DI KECAMATAN PAKAL SURABAYA - Dwi Hardaningtyas; Dewi Suprobowati (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2020)
The purpose of educational innovation is to create superior humans, superior quality humans who are able to see and take advantage of existing opportunities to improve their standard of living. In line with the aim of educational innovation, namely to create superior quality human beings who are creative, adaptive and competitive to change. So the role of the Principal is very important. This means that the principal's performance is a very determining factor for the quality of learning / education which will have implications for the quality of education output. Schools that are developing and advanced and have excellent graduates are usually led by a principal who has a good performance as well. The principal has a big responsibility to make it happen. Therefore, a principal who is professional and has productive behavior is needed to overcome the various problems that come to the world of education. This demand leads to the importance of productive behavior that must be possessed by school principals. The principal has an important role in the implementation of school education so that teachers can work optimally to achieve educational goals. This study aims to analyze the productive behavior of the Principals of Public Elementary Schools in Pakal District of Surabaya based on their Psychological Capital (PsyCap) as well as the current organizational culture. This study uses a quantitative approach. Data obtained through a questionnaire that measures the variable Psychological Capital (PsyCap), Organizational Culture and productive behavior. This questionnaire was given to all school principals in Pakal District, totaling 6 people. Data were analyzed statistically with the Multiple Linear Regression Analysis technique. To simplify the calculation of data in this study, researchers used the SPSS version 23 software application.